2011
DOI: 10.1128/jcm.01657-10
|View full text |Cite
|
Sign up to set email alerts
|

The rtxA Toxin Gene of Kingella kingae: a Pertinent Target for Molecular Diagnosis of Osteoarticular Infections

Abstract: Kingella kingae is an emerging osteoarticular pathogen in young children. Its isolation by traditional culture methods remains difficult, underscoring the need to implement other diagnostic methods for its detection and identification, such as nucleic acid amplification tests. Although the genome of this bacterium has not yet been sequenced, a toxin named RTX has been identified. The goal of this study was to develop sensitive, specific, and rapid molecular methods based on the rtxA toxin gene sequence to diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 24 publications
2
73
0
1
Order By: Relevance
“…All K. kingae clinical strains possess the rtxA toxin gene, making this gene a relevant target to diagnose K. kingae infection by PCR. However, there is a polymorphism of the rtxA gene, which encodes the RTX toxin [48], and a few studies have demonstrated that the most virulent strains of the species harbored a 33-bp duplication or triplication in their rtxA sequence, suggesting that this genetic trait could represent a genetic determinant of virulence [48,49]. Finally, Bendaoud et al reported that K. kingae forms biofilms in a microtiter plate assay [50].…”
Section: Rtx Toxin Productionmentioning
confidence: 99%
“…All K. kingae clinical strains possess the rtxA toxin gene, making this gene a relevant target to diagnose K. kingae infection by PCR. However, there is a polymorphism of the rtxA gene, which encodes the RTX toxin [48], and a few studies have demonstrated that the most virulent strains of the species harbored a 33-bp duplication or triplication in their rtxA sequence, suggesting that this genetic trait could represent a genetic determinant of virulence [48,49]. Finally, Bendaoud et al reported that K. kingae forms biofilms in a microtiter plate assay [50].…”
Section: Rtx Toxin Productionmentioning
confidence: 99%
“…It is possible that prolonged carriage induces strain-specific immunity that facilitates elimination of the carried organism but does not prevent acquisition of an antigenically different strain. This possibility is supported by the demonstration of strain-to-strain variability of K. kingae outer-membrane proteins [37], the PilA1 gene encoding the major pilus subunit [17], and the RTX toxin [10,13], suggesting that immunogenic surface-exposed bacterial components involved in pharyngeal colonization, undergo antigenic variation to evade the host's immune response.…”
Section: Colonization Dynamics and Turnover Of Strainsmentioning
confidence: 63%
“…The nucleic acid amplification assays developed to amplify conserved segments of the RTX toxin endoding genes rtxA and/or rtxB are able to detect 30 colony forming units (c.f.u.) of the organism, exhibiting a higher sensitivity than that of broad range 16S rRNA [12,14] or the cpn60 gene PCR tests [13], are highly specific, can be applied to a variety of clinical specimens, and enable detection of strains exhibiting RTX locus polymorphisms [10][11][12][13][14].…”
Section: Nucleic Acid Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Al romperse la barrera epitelial el proceso es potencialmente mediado por una toxina extracelular de tipo RTX, con capacidad de lisar células epiteliales, sinoviales y macrófagos, que permite la diseminación a través del torrente sanguíneo a sitios distales, como huesos y articulaciones. 7,8 La fase de bacteriemia transitoria es corta y asintomática, lo que explica la frecuente negatividad de los hemocultivos.…”
Section: Comentariounclassified